ERP, Ciborgues e Memórias Protéticas - Ludmer, Gilson (Teoria e Prática em Administração, 2011)
ERP systems have profound impacts on businesses processes and on the knowledge that employees need to carry out their activities. This essay discusses the ERP phenomenon using the metaphor of the cyborg and concepts about prosthetic memory based on the works of Haraway (2000) and Landsberg (1995). These works are used to explore aspects of ERP that seem to be otherwise obscure or camouflaged, so in need to be revealed. The cyborg can contribute to the understanding of different ways in which science and technology affect our lives, subjectivity and concepts. Issues such as complexity, changes in the workforce, changes in control strategies, identity and potential influences on knowledge and organizational actions related with ERP systems are interpreted in this essay. Finally, some questions and recommendations are presented on how to work with ERP systems.